Epidemiology of human and animal leptospirosis in Kenya: A systematic review and meta-analysis - Wainaina, M.; Wasonga, Joseph; Cook, Elizabeth A.J. (International Livestock Research Institute, 2024)
Key messages Wide host range and considerable pooled seroprevalence in cattle and goats revealed the need for control in animal hosts. Raising awareness among farmers, health and veterinary professionals is needed for early recognition, diagnosis, and management. Rapid diagnostic tests and microscopic agglutination tests are needed for timely and accurate leptospirosis diagnosis. Molecular approaches needed to understand the circulating serovars and strain diversity for the effective control of leptospirosis.